2010
DOI: 10.1111/j.1365-246x.2009.04426.x
|View full text |Cite
|
Sign up to set email alerts
|

Spectral induced polarization of partially saturated clay-rocks: a mechanistic approach

Abstract: International audienceWe have developed a mechanistic model to interpret spectral induced polarization data of partially saturated clay-rocks. This model accounts for the polarization of the grains through an electrical double layer model with a polarization model of the inner part of the electrical double layer called the Stern layer. The polarization model accounts also for the Maxwell-Wagner polarization at frequencies higher than 100 Hz. The Maxwell-Wagner polarization is modelled by using a conductivity m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
153
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 135 publications
(165 citation statements)
references
References 55 publications
9
153
3
Order By: Relevance
“…In various studies it has been found that the ionic mobility of the counterion species in the Stern and diffuse layers is close to the mobility of this species in the bulk pore electrolytic solution b + f [e.g., Tarasov and Titov, 2007;Leroy et al, 2008]. This can be explained by the location of the counterion on the outer Helmholtz plane of the Stern layer, where it keeps its hydration shell [Tournassat et al, 2009;Jougnot et al, 2010;Revil and Florsch, 2010]. This might be different for counterion species with a higher affinity to the mineral surface and for minerals with permanent structural charges on their basal surface (e.g., illite and smectite) [Leroy and Revil, 2009].…”
Section: Ec Polarizationmentioning
confidence: 98%
See 2 more Smart Citations
“…In various studies it has been found that the ionic mobility of the counterion species in the Stern and diffuse layers is close to the mobility of this species in the bulk pore electrolytic solution b + f [e.g., Tarasov and Titov, 2007;Leroy et al, 2008]. This can be explained by the location of the counterion on the outer Helmholtz plane of the Stern layer, where it keeps its hydration shell [Tournassat et al, 2009;Jougnot et al, 2010;Revil and Florsch, 2010]. This might be different for counterion species with a higher affinity to the mineral surface and for minerals with permanent structural charges on their basal surface (e.g., illite and smectite) [Leroy and Revil, 2009].…”
Section: Ec Polarizationmentioning
confidence: 98%
“…Leroy and Revil [2009] mention that membrane polarization might make a significant contribution to effective polarization at low frequencies (f < 1 Hz), at least in clays. Nevertheless, as demonstrated in various publications, the SIP response of sands and clays can be modeled from EC mechanisms without requiring any flush factor [e.g., Leroy et al, 2008;Leroy and Revil, 2009;Jougnot et al, 2010;Revil and Florsch, 2010]. We assume, therefore, that EC polarization makes the dominant contribution to the effective polarization occurring in sandstones in the investigated frequency range.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The imposed injection voltage is set to 1 V. The measured phase is typically below 50 mrad, and most of the cases below 10 mrad imposing the use of very rigorous procedures including (1) the use of 4 electrodes configuration, (2) electrodes with small phase errors and input impedances, (3) the minimization of potential electromagnetic couplings at high frequencies (i.e., minimizing metallic parts in the sample holders), (4) very stable electrodes for the low frequency measurements (i.e., no drifts), and (5) a correction procedure for equivalent circuit of the system without the core samples. The phase accuracy is typically around 0.1-0.2 mrad below An important point in the evaluation of the electrical conductivity is the determination of the geometrical factor (or cell constant) of the sample holder (e.g., Jougnot et al [2010]). …”
Section: Complex Conductivity Measurementsmentioning
confidence: 99%
“…the reversible storage of electrical charges) of porous materials (Kemna et al 2012). Polarization of oxides and carbonates minerals such as calcite is related to the polarization of the electrical double layer (EDL) surrounding the particles under an external alternating current or electrical field (Chelidze & Gueguen 1999;Jougnot et al 2010;Revil & Florsch 2010). When a sinusoidal current at a range of frequencies is applied to the charged porous medium and the resulting difference of electrical potential is measured, complex conductivity is referred to as spectral induced 124 P. Leroy et al polarization (SIP) (Collet 1990;Weller & Borner 1996;Luo & Zhang 1998;Huisman et al 2015).…”
Section: Introductionmentioning
confidence: 99%